Developing a German-English Dictionary of the Common Language of Academia - Rheindorf, Markus; Huemer, Birgit (Journal of Academic Writing, 2015)
The factual dominance of English as Lingua Franca of the international scientific community continues to increase in most disciplines. Univesrity students, lecturers and researchers are more and more commonly required to acquire English for academic purposes. Meanwhile, linguistic research into the similarities and differences between academic English and its German, Italian or other counterparts has been conducted. However, no comprehensive study has yet dealt with the specific problems faced by German-speaking academics and students acquiring English for academic purposes. It is in this context that this article presents an ongoing research project designed to address that gap. It concerns the lack or partial lack of equivalent linguistic means between the German and the English common language of academia. The common language of academia is, by definition, used across the disciplines and contains or realises fixed, language- and culture-specific conceptions of what actually constitutes 'science' or 'academia'. It is largely based on but differs from language use in everyday contexts, thus posing significant challenges for students even in their first language. In this article, we address the challenge of achieving not only a functional comparison of the common language of academia in English and German, but of complementing the underlying inventory and analysis of each. Following a discussion of previous work, we detail our research design and criteria for the comparative analysis of the common language of academia in English and German, as well as some prelimiary results of the project. The findings of our project will ultimately lead to a German-English dictionary for the common language of academia designed to support both students and academics with understanding and participating in international scientific communities with different linguistic backgrounds.